Pengaruh Usia Dan Pendidikan Terhadap Implementasi nisiasi Menyusu Dini (IMD) Pada Pasien Post Sectio Caesarea - Meylina Parela Ningsih; FX. Ady Soesetijo; Dewi Rokhmah (Multidisciplinary Journal, 2021)
Early initiation of breastfeeding (EIBF) in post sectio caesarea patients is the process of breastfeeding the baby to his mother immediately after birth by placing the baby on the mother's chest or abdomen so that skin-to-skin contact occurs and letting the baby find the mother's nipple and then breastfeed until satisfied. The benefits of IMD are very large for mothers and babies including accelerating the production of colostrum as a baby antibody so as to prevent infection, prevent hypothermia and hypoglycemia and prevent anemia due to bleeding after delivery. IMD becomes important to be carried out both for mothers with normal labor and with the act of sectio caesarea. This study aims to determine the effect of maternal age and education on the implementation of early initiation of breastfeeding (IMD) in post sectio caesarea patients. This type of research was analytic observational with cross sectional design. Data obtained from primary data 99 respondents by filling out a questionnaire and direct observation. The research site at Bina Sehat Jember Hospital in April 2021. Data obtained from the primary data of 99 respondents by filling out questionnaires and making direct observations. Data analysis used is bivariate analysis using SPSS statistical data processing tool. The results of the instrument test show that all variables were valid and reliable as a data collection tool. The results of data analysis showed that: 1) Age had no significant effect on the implementation of IMD in post sectio caesarea patients (p = 0.769) because the indication for delivery by sectio caesarea was not carried out in patients with high risk age, but also in productive age. 2) Education had no significant effect on the implementation of IMD in post sectio caesarea patients (p = 0.284) Because knowledge about the importance of early breastfeeding initiation and how to do it is not obtained during formal education but from non-formal education and other educational media, so that other educational media are needed in order to support the implementation of IMD, especially in post sectio cesarea patients. Keywords: Early Initiation Breastfeeding, Education, Sectio Caesarea, Age